Effect of computer assisted presentation regarding antenatal diet in Knowledge among antenatal mother at primary health centre - S.JOSE AMALA ANILDA BSC (N) CLINICAL INSTRUCTOR. (International Journal of Pharma and Bio Sciences, 2017)
Antenatal Period is a very crucial period for both mother and fetus.. Adequate nutrition during pregnancy is important to enable to fetus to grow and develop physically and mentally to full potential. It is widely believed that fetal nutrition plays a key role is the well-being of the newborn. The need for study is to show the effectiveness of computer assisted presentation regarding antenatal diet in knowledge among antenatal mother objectives: To assess the knowledge regarding antenatal diet among antenatal mother, To assess the effect of computer assisted presentation regarding antenatal diet among antenatal mother, To associate the posttest level of knowledge of antenatal mothers regarding antenatal diet with selected demographic variables. Methodology: Research approach Quantitative approach Research design: One group pre and post test design. Result: In posttest 37 mothers(62%)have gained adequate knowledge,23 mothers(38%)have gained moderately adequate knowledge and nobody have inadequate knowledge about antenatal diet after computer assisted presentation.